Assessing judicial activism of the CJEU the case of the court's defence procurement rulings. Issue 4 (19th May 2019) - Terpan, Fabien; Saurugger, Sabine
ABSTRACT: The aim of this article is to assess the judicial activism of the Court of Justice of the European Union. In adopting a politics-of-law approach, the article contributes to the more recent literature which stresses that the Court's activism can only be understood by embedding the analysis of its rulings in the broader political and institutional context of European integration. Based on the analysis of the Court's two defence procurement rulings, the article argues that the Court has limited the member states' capacity to refer to article 346 TFEU which aims to protect the member states' essential security interests and to allow them to escape the EU's public procurement rules. Not only has the Commission used the threat of a Court ruling to convince the member states to legislate in this field but the Court has also issued activist rulings, albeit moderately activist ones.